Research into Spinal Deformities 4 : Research into Spinal Deformities 4. - Grivas, Th. B. (Studies in health technology and informatics., 2002)
This publication consists of a wide range of topics on Spinal Deformities, which include: Aetiology, Incidence, Natural History and Prognosis, Genetics and Growth, Anatomy, Pathology and Basic Science, Assessment, Biomechanics, Gait, Surface Topography, Imaging, Morphological Aspects (3-D) of Spinal Deformity, Technology, Cervical Spine, Spondylolisthesis - Low Back Pain, Conservative Treatment - (Physiotherapy-Brace), Surgical Treatment and Outcome. These essays were presented at the annual meeting of the International Research Society of Spinal Deformities (IRSSD). Particular interest is giv.